TRAINING VILLAGE TENURE RIGHTS ON COASTAL LAND VS VILLAGE ULAYAT IN UNGASAN TRADITIONAL VILLAGE - Ni Komang Rai Widhyaningsih; I Made Suwitra (NOTARIIL Jurnal Kenotariatan, 2023)
This paper analyzes the Customary Village Tenure Rights on Coastal Land as Village Customs in the Ungasan Traditional Village. The focus of the study in this paper is on land that has been certified and Ulayat land is joint land with the members of the customary law community concerned. The research method used in this paper is an empirical legal research method using the Legal Approach, Analytical, Case Approach, Customary Law Approach, and Legal Sociology Approach. The analysis of legal materials in this paper is carried out by using several legal theories, namely Legal Certainty Theory, Authority Theory, Justice Theory, and Benefit Theory where these theories will later serve as analytical tools in discussing legal issues in this study. It can be concluded that the right of control over customary land to coastal land follows the concept of control rights regulated in Article 33 paragraph (3) of the 1945 Constitution in conjunction with Article 2 Paragraph (1) of the BAL. The regulation on the use of coastal land controlled by the Ungasan Traditional Village has been stated and regulated clearly as it turns out in the Ungasan Traditional Village Awig-Awig and Ungasan Traditional Village Perarem Number 06 of 2020, it can be seen that there are clear arrangements relating to the use of coastal land areas in the Ungasan Village. Ungasan Traditional Village. In relation to the authority of the Ungasan Traditional Village on the utilization of the coastal land area in its territory, it is based on the existence of the customary land rights owned by the Ungasan Traditional Village based on Article 18 of the 1945 B UUD.